Assessment of Peak Oxygen Uptake with a Smartwatch and its Usefulness for Training of Runners - Düking, Peter; Van Hooren, Bas; Sperlich, Billy (International Journal of Sports Medicine, 2022)
Peak oxygen uptake (˙VO2peak) is an important factor contributing to running performance. Wearable technology may allow the assessment of ˙VO2peak more frequently and on a larger scale. We aim to i) validate the ˙VO2peak assessed by a smartwatch (Garmin Forerunner 245), and ii) discuss how this parameter may assist to evaluate and guide training procedures. A total of 23 runners (12 female, 11 male; ˙VO2peak: 48.6±6.8 ml∙min−1∙kg−1) visited the laboratory twice to determine their ˙VO2peak during a treadmill ramp test. Between laboratory visits, participants wore a smartwatch and performed three outdoor runs to obtain ˙VO2peak values provided by the smartwatch. The ˙VO2peak obtained by the criterion measure ranged from 38 to 61 ml∙min−1∙kg−1. The mean absolute percentage error (MAPE) between the smartwatch and the criterion ˙VO2peak was 5.7%. The criterion measure revealed a coefficient of variation of 4.0% over the VO2peak range from 38–61 ml∙min−1∙kg−1. MAPE between the smartwatch and criterion measure was 7.1, 4.1 and −6.2% when analyzing ˙VO2peak ranging from 39–45 ml∙min−1∙kg−1, 45–55 ml∙min−1∙kg−1 or 55–61 ml∙min−1∙kg−1, respectively.
Keywords: data-guided training; digital health; digital training; eHealth; innovation; technology; wearable; mHealth